THE EFFECTIVENESS OF COMBINATION OF SNAKEHEAD FISH, TEMULAWAK, AND MENIRAN EXTRACTS ON POST OVARIOHYSTERECTOMY WOUND HEALING IN CATS - Bermani, Fadeli; Soehartono, Raden Harry; Berlian, Guntur; Siswandi, Riki (Universitas Syiah Kuala, 2024)
This study aims to determine the effectiveness of combination of snakehead fish, ginger and meniran extract (GTM) on healing wounds after ovariohysterectomy (OH) in cats. Twenty healthy female cats aged 1-4 years, weighed 2-4 kg were divided into three groups with different doses of GTM and compared with the group without treatment (n= 5 cats/group). The GTM dose was extrapolated from the human dose using allometric scaling, with the basal dose for G:T:M were 40:3.2:4.8 mg/kg BW (group 1, GTM1x). Treatment groups 2 (GTM2x) and 3 (GTM4x) were given a dose of GTM that was multiplied by 2 and 4 of the basal doses, respectively. OH was performed via a flank approach with the same operator and anesthesia. Discharge, swelling and erythema scores were significantly lower on days 3, 4 and 5 post-operativeamong all GTM groups compared with control. Pain evaluation using Baseline Tactile Semmes Monofilaments showed significantly lower in GTM2x and GTM4x compared to GTM1x and control. The 4A-vet pain scale showed lower pain in GTM2x from 1 to 5 days postoperative. The number of leukocytes, erythrocytes and platelets was in the normal range indicates the absence of postoperative infection. Postoperative albumin levels showed a significantly higher difference in GTM2x compared to control. The treatment given GTM2x showed the fastest healing interval (3.20.44 days). The combination of GTM can reduce pain, reduce wound scores and accelerate post-OH wound healing with the most effective dose was GTM2x. ________________________________________________________________